ผลกระทบของการเปลี่ยนสภาพภูมิอากาศต่อปริมาณนํ้าท่าในอ่างเก็บนํ้าเอนกประสงค์ (Impact of Climate Change on Inflow in Multi-Purpose Reservoir) - พวงชมภู พงศกร; ประสารฉํ่า หริส (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2016)
บทคัดย่อ การเปลี่ยนแปลงสภาพภูมิอากาศโลกส่งผลกระทบต่อปริมาณนํ้าท่าในแหล่งนํ้าระหว่างช่วงฤดูฝนและ ฤดูแล้ง โดยเฉพาะอ่างเก็บนํ้าที่ใช้ประโยชน์เพื่อการส่งนํ้าเพื่อผลิตนํ้าประปาและเกษตรกรรม การศึกษานี้ มีวัตถุประสงค์เพื่อศึกษาผลกระทบของการเปลี่ยนแปลงปริมาณฝนต่อปริมาณนํ้าท่าที่ไหลเข้าสู่อ่างเก็บนํ้า ห้วยสีทน จังหวัดกาฬสินธุ์ โดยใช้แบบจำลอง PRECIS เพื่อคาดการณ์ปริมาณฝนกรณี B2 ของ IPCC SRES และวิเคราะห์ข้อมูลในอดีตด้วยวิธีสหสัมพันธ์เพื่อสร้างสมการประเมินปริมาณ นํ้าท่าระหว่าง พ.ศ. 2557 - 2566 เทียบกับข้อมูลปีฐานระหว่าง พ.ศ. 2549 - 2556 ผลการศึกษาพบว่า ปริมาณฝนและปริมาณนํ้าท่าในช่วงคาดการณ์เมื่อเทียบกับปีฐานมีค่าเฉลี่ยลดลง 5.2 มิลลิเมตร ต่อปี และ 0.04 ล้านลูกบาศก์เมตรต่อปี ซึ่งชี้ให้เห็นว่าปริมาณนํ้าท่ามีแนวโน้มลดลงจนเป็นสาเหตุ ของการเกิดภาวะภัยแล้งในอนาคต วิธีการและผลของการศึกษาในครั้งนี้จึงคาดว่าจะสามารถนำไป ประยุกต์ใช้เพื่อเป็นข้อมูลการตัดสินใจสำหรับการจัดการนํ้าเพื่อการอุปโภค - บริโภคและการเกษตรกรรม โดยหน่วยงานที่รับผิดชอบได้ในอนาคต Abstract The global climate change affects the inflow volumes in water resources in-between rainy season and dry season, especially, in the reservoirs, mainly designed for the purposes of water supply and agricultural. This study aims to examine the effects of the rainfall changes towards the inflows volumes at the Huay-Srithon Reservoir, situated in Kalasin province by using the PRECIS Model to predict the rainfall in case of B2-IPCC SRES, and to analyze the historical data by using the method of correlation that leads to an equation used for evaluating inflows volume of the reservoir during the years 2014 - 2023 comparing to the base line year from the years 2006 - 2013. The results reveal that inflows volumes and rainfall levels are both decreased comparing to base line year at 5.2 mm per year and 0.04 MCM per year, respectively. It indicates the inflows volumes are likely to decline and can be referred as a cause of drought situation in nearly future. In the long run, the research methodology and results of this study are expected to enhance the decision-making of the agencies that are responsible for water management in aspects of water consumption and agriculture usages.